Organising the only game in town - Desai, Meghnad (1996)
The World Trade Organisation - the result of a revolutionary international agreement - meets for the first time in December in Singapore. It is a symbolic start for a new process which, among other things, offers countries from the South an important voice in global economic affairs. Lord Desai argues that, although power and procedures may not be fairly divided, the world has, for the first time this century, agreed its economic agenda. - Reproduced
Keywords: International trade; World Trade Organization